Understanding the roles of anionic redox and oxygen release during electrochemical cycling of lithium-rich layered Li4FeSbO6 - McCalla, Eric; Sougrati, Moulay Tahar; Rousse, Gwenaelle; Berg, Erik Jamstorp; Abakumov, Artem; Recham, Nadir; Ramesha, Kannadka; Sathiya, Mariyappan; Dominko, Robert; Van Tendeloo, Gustaaf; Novák, Petr; Tarascon, Jean-Marie (Journal of the American Chemical Society, 2015)
Li-rich oxides continue to be of immense interest as potential next generation Li-ion battery positive electrodes, and yet the role of oxygen during cycling is still poorly understood. Here, the complex electrochemical behavior of Li4FeSbO6 materials is studied thoroughly with a variety of methods. Herein, we show that oxygen release occurs at a distinct voltage plateau from the peroxo/superoxo formation making this material ideal for revealing new aspects of oxygen redox processes in Li-rich oxides. Moreover, we directly demonstrate the limited reversibility of the oxygenated species (O2(n-); n = 1, 2, 3) for the first time. We also find that during charge to 4.2 V iron is oxidized from +3 to an unusual +4 state with the concomitant formation of oxygenated species. Upon further charge to 5.0 V, an oxygen release process associated with the reduction of iron +4 to +3 is present, indicative of the reductive coupling mechanism between oxygen and metals previously reported. Thus, in full state of charge, lithium removal is fully compensated by oxygen only, as the iron and antimony are both very close to their pristine states. Besides, this charging step results in complex phase transformations that are ultimately destructive to the crystallinity of the material. Such findings again demonstrate the vital importance of fully understanding the behavior of oxygen in such systems. The consequences of these new aspects of the electrochemical behavior of lithium-rich oxides are discussed in detail.